Semisynthesis of C17:0 isoforms of sulphatide and glucosylceramide using immobilised sphingolipid ceramide N-deacylase for application in analytical mass spectrometry - Kuchar, L; Rotková, J; Asfaw, B; Lenfeld, J; Horák, D; Korecká, L; Bílková, Z; Ledvinová, J (Rapid communications in mass spectrometry, 2010)
Sphingolipid ceramide N-deacylase (SCDase, EC 3.5.1.69) is a hydrolytic enzyme isolated from Pseudomonas sp. TK 4. In addition to its primary deacylation function, this enzyme is able to reacylate lyso-sphingolipids under specific conditions. We immobilised this enzyme on magnetic macroporous cellulose and used it to semisynthesise C17:0 glucosylceramide and C17:0 sulphatide, which are required internal standards for quantification of the corresponding glycosphingolipids (GSL) by tandem mass spectrometry. A high rate of conversion was achieved for both lipids (80% for C17:0 sulphatide and 90% for C17:0 glucosylceramide). In contrast to synthesis with a soluble form of the enzyme, use of immobilised SCDase significantly reduced the contamination of the sphingolipid products with other isoforms, so further purification was not necessary. Our method can be effectively used for the simple preparation of specifically labelled sphingolipids of high isoform purity for application in mass spectrometry.
Keywords: Pseudomonas; enzymy imobilizované; Sulfoglycosphingolipids; Enzymes, Immobilized; Stereoisomerism; Glucosylceramides; sulfoglykosfingolipidy; Reference Standards; Mass Spectrometry; referenční standardy; glykosfingolipidy; Bacterial Proteins; Glycosphingolipids; stereoizomerie; Amidohydrolases; amidohydrolasy; glukosylceramidy; Hydrolysis; hydrolýza; bakteriální proteiny; hmotnostní spektrometrie